Renewable Energy and Human Resource Development: Challenges and Opportunities in Indonesia - Udin, Udin (International Journal of Energy Economics and Policy, 2020)
The availability of renewable energy and quality human resources is expected to be a major factor to bring Indonesia to reach glory in 2045. Therefore, this paper aims to investigate and explore the challenges and opportunities for renewable energy and human resource development in Indonesia. This paper uses conceptual and systematic review analysis to highlight the special issue of renewable energy and human resource development. This paper reveals that renewable energy and human resource development become a great foundation of Indonesia needs in the future. Keywords: Renewable energy, human resource development JEL Classifications: Q20, Q28, O15 DOI: https://doi.org/10.32479/ijeep.8782